ANALISIS IMPLIKASI PERPAJAKAN PADA TRANSAKSI BUILT OPERATE TRANSFER (BOT), LEASING DENGAN HAK OPSI, JOINT OPERATION, YAYASAN - Pakpahan, Kristina; Najib, Ahmad; Pahala, Indra (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to critically examine the application of taxation to various forms of special transactions that often occur in practice in Indonesia, namely the Build Operate Transfer (BOT) scheme, leasing with option rights, joint operations (JO), and foundation legal entities. These four forms of transactions have unique characteristics that are not always in line with general tax principles, thus creating complexity in the imposition, deduction, reporting, and application of taxation. The research approach used is qualitative descriptive with data collection techniques through literature studies, tax regulation documentation, and critical analysis of academic literature. The results of the study indicate that there are still inconsistencies between accounting and taxation treatments, weak recording, and unpreparedness of actors in fulfilling tax obligations substantively. The BOT scheme often results in recognition of income between the private sector and the government; leasing with option rights creates different treatments between lessees and lessors in terms of VAT and Income Tax; JO faces administrative challenges due to the absence of a separate NPWP; while foundations face the risk of fiscal correction due to the combination of social and commercial activities without limitations on capable accounts. This study recommends increasing the capacity of tax human resources, reformulating technical regulations, and integrating a digital-based reporting system that is more responsive to the characteristics of special transactions.